Assessment of self-reported financial toxicity among patients with nasopharyngeal carcinoma undergoing radiotherapy: A cross-sectional study in western China - Jiang, Hua; Mou, Wenxuan; Lyu, Jianxia; Jiang, Luxi; Liu, Ying; Zeng, Yu; Hu, Aiping; Zheng, Wei; Jiang, Qinghua; Yang, Shuang (Frontiers in Oncology, 2022)
Objective Using the Comprehensive Score for Financial Toxicity (COST) tool to measure financial toxicity (FT) among nasopharyngeal cancer (NPC) patients in western China and investigate the association between FT and psychological distress. Methods We conducted a cross-sectional study of survivors with NPC in a tertiary oncology hospital in China. FT was assessed using the COST (Chinese version) instrument, validated, and widely used internationally and in China. The NCCN Distress Thermometer (DT) was used to measure psychological distress. A multivariate logistic regression model was built to determine factors associated with FT, and the Pearson correlation was used to assess the correlation between COST and DT scores. Results Of 210 patients included in this study, the mean FT score was 16.3 (median 22.5, SD 9.7), and the prevalence of financial toxicity was 66.2%. Of these, 37.1% were mild FT, 50.5% were moderate FT, and 2.4% were severe FT. In Logistic regression model, 6 variables were associated with increased FT: live in the countryside, unmarried, unemployed, advanced cancer, and received targeted therapy, lower annual household income. The Pearson correlation showed a strong correlation between financial toxicity and psychological distress (r= -0.65, P < 0.001). Conclusion Patients with nasopharyngeal carcinoma (NPC) in western China reported a higher proportion of self-reported financial toxicity (FT), associated with unmarried, unemployed, lower income, advanced cancer, and received targeted therapy. Clinicians should identify patients by predictors early and conduct psychological interventions.